The Humiliation Toward Women Asseen in Henrik Ibsen’s Doll’s House - Mac Aditiawarman; Octa Deski Aryan (Jurnal Ilmiah Langue and Parole, 2019)
This research is a study of Ibsen's A Doll’s House from the perspective of justice for women. The purpose of this research is to find out and explain the types of women's problems faced by female main characters, to identify and describe the struggles of the main female characters in gaining independence in their lives, and to find out the significant meaning behind the success of the main female leaders' struggles as represented in drama. Implemented to answer the objectives of this study. This study is a qualitative study described by Creswell.The object of this study is Ibsen's Doll House. This research uses Wolffrey, Robbins, and Womack's theories about men totally controlling women, without any women's rights. There is also the theory of Faqih, and Kate Millet. The formulation of the problem in this study are (1) What types of problems are faced by the main female characters in A Ibsen Doll House? (2) How did the main female character face problems for her independence at A Ibsen Doll House? (3) What is the significance behind the success of the struggle of the main female character in gaining independence in her life at A Ibsen Doll House? Here we see the social side of this drama is very distorted. It teaches us as human beings to respect each other against men and women, so that there are no gaps in marriage. In conclusion, this study aims for all people to do justice to fellow human beings, whether male or female, in order to live peacefully.